EFFECT OF SARGASSUM ILICIFOLIUM ON OVOGENESIS IN PCOS INDUCED RATS - J, Anbu; K, Sukanya; S, Santhosh Kumar; Reddy, Ramya PS; Nandihalli, Vani B (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: This study was conducted to evaluate the effect of Sargassum ilicifolium (S. ilicifolium) on Testosterone induced Polycystic Ovary Syndrome (PCOS) in rats. Methods: Female Wistar albino rats were divided into 6 groups consisting of 6 rats each. PCOS was induced in all the animals except normal group on administration of Testosterone (2 mg/100 g) for 21 d daily. After PCOS induction the standard group rats were treated with Clomiphene citrate (CC) (1 mg/kg p.o.). The test groups were treated with 100, 200 and 400 mg/kg of ethanolic extract of Sargassum ilicifolium (EESI) orally and normal animals were administered 2% CMC (2 ml/kg) respectively for 21 d. During induction and treatment period various parameters like oestrus cycle, histopathology, hormonal and biochemical assays have been evaluated. Further to confirm the enhanced fertility rate, the rats were mated and the litter size was observed. Results: The results revealed the normalcy in oestrus cycle, hormonal, biochemical and histopathological parameters. The litter size was increased significantly compared to control. Conclusion: Overall, from the obtained results it is determined that the S.Â ilicifolium exhibited a good anti-androgenic effect by reducing the Testosterone levels in PCOS induced conditions. Â